Jalpaneca Aristocracy, the popular poem by Salomé Taracena Gallegos - PRIEGO MARTINEZ, JORGE (Cinzontle, 2024)
When I was studying primary school in this city of Villahermosa, for the first time I heard the nice and popular poem Aristocracia Jalpaneca, original by Salomé Taracena Gallegos, the famous “Melenudo Negro”. Almost always at the school celebrations of those years, throughout Tabasco, one could hear this exhilarating poem written in octosyllabic verses, full of substance, humor, mischief and biting criticism, which was liked by all audiences.